2009
DOI: 10.1007/s00011-009-7100-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutrophil infiltration by a malleable protein matrix of lactic acid bacteria-fermented whey proteins in vivo

Abstract: MPM administration demonstrates a significant reduction of neutrophil infiltration associated with an inhibition of cytokine and chemokine production. The air pouch model shares similarities with in vivo characteristics of rheumatoid arthritis and neutrophilic diseases, both of which would benefit from this 50% inhibition of neutrophil infiltration induced by MPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In line with our findings, Sprong et al ( 1 ) reported that cheese whey protein protected rats against mild dextran sulphate Na-induced colitis by inhibiting the expressions of inflammatory cytokines. Whey product has demonstrated a number of anti-inflammatory effects including decreased cytokine release in rodent models after exposure to LPS ( 42 ) . It is possible that the protective effects of WPC supplementation on intestinal integrity were closely related to reducing the expressions of intestinal pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Sprong et al ( 1 ) reported that cheese whey protein protected rats against mild dextran sulphate Na-induced colitis by inhibiting the expressions of inflammatory cytokines. Whey product has demonstrated a number of anti-inflammatory effects including decreased cytokine release in rodent models after exposure to LPS ( 42 ) . It is possible that the protective effects of WPC supplementation on intestinal integrity were closely related to reducing the expressions of intestinal pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also shown that MPM, upon oral gavage in diet-induced obese mice, may act as a potential peroxisome proliferator-activated receptor gamma (PPARγ) agonist (Lapointe et al, 2009). This could occur indirectly via the action of MPM on insulin or via reduction of specific cytokines and inflammation markers, considering the antiinflammatory effect of MPM and its ability to inhibit cytokine and chemokine production (i.e., IL-1β, IL-6, and tumor necrosis factor-α) in murine immune disease models (Beaulieu et al, 2007b(Beaulieu et al, , 2009a.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found that [40]. In addition, many studies reported that probiotics, and homogenates of lactic acid bacteria are effective for preventing cancer [29], improving absorption of lactose and milk proteins [15], decreasing cholesterol [42], treating rheumatoid arthritis [5], and enhancing intestinal regulation [20]. Thus, in terms of the functionality of lactic acid bacteria, this study confirmed that antimicrobial and anti-allergic activity was increased by culturing the lactic acid bacteria in a medium containing the supernatant of lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…casei had strain-specific therapeutic effects on allergy [25,40]. Various studies also showed that probiotics, killed lactic acid bacteria, and lactic acid bacteria lysates induced anti-cancer effect [29], improved absorption of lactose and milk proteins [15], lower serum cholesterol levels [42], treatment for rheumatoid arthritis [5], and intestinal regulation [20].…”
Section: Introductionmentioning
confidence: 99%